(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This study rigorously examines the economic dynamics instigated by the proliferation of digital currencies, probing their intricate implications for traditional banking infrastructures and the overarching global economic paradigm. Employing advanced economic and academic lexicon, our analysis dissects the technological disruptions precipitated by digital currencies, elucidates their catalytic role in engendering financial inclusion, and scrutinizes the nuanced evolution of central bank engagement.